2014
DOI: 10.1021/cm500980b
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Hydrazinidoborane: A Polymorphic Material with Potential for Chemical Hydrogen Storage

Abstract: Metal amide and hydrogen (MNH2-H2) system is recognized as a promising reversible hydrogen storage system due to its high hydrogen capacity and lower operating temperature. However, slow reaction rate for the Li system with the highest hydrogen capacity is an important issue to be solved for practical use. In this thesis, modification of the reaction properties for the LiNH2-H2 system is carried out from thermodynamic and kinetic points of view. Particularly, the novel ammonia synthesis technique is proposed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 33 publications
(110 reference statements)
13
40
0
Order By: Relevance
“…The patterns obtained for the temperature range 81-301 K were indexed in the monoclinic phase with the space group P2 1 /c ( Figure S14). The unit cell parameters (Table 1) are in good agreement with those reported elsewhere [13,15]. The unit cell parameter c presents a negative coefficient of thermal expansion (Figure 8).…”
Section: Lithium Hydrazinidoborane Lihbsupporting
confidence: 87%
See 1 more Smart Citation
“…The patterns obtained for the temperature range 81-301 K were indexed in the monoclinic phase with the space group P2 1 /c ( Figure S14). The unit cell parameters (Table 1) are in good agreement with those reported elsewhere [13,15]. The unit cell parameter c presents a negative coefficient of thermal expansion (Figure 8).…”
Section: Lithium Hydrazinidoborane Lihbsupporting
confidence: 87%
“…For example, the polymorphic derivative lithium hydrazinidoborane (LiHB) is obtained by ball-milling HB and LiH in equimolar amounts, and depending on the milling conditions, two different phases can be obtained. The β phase, β-LiHB, is orthorhombic with a space group Pbca [13]. It is in fact the low-temperature phase.…”
Section: Introductionmentioning
confidence: 99%
“…This result is surprising, as even for amidoboranes, such an unexpected substitution has never been observed [21]. Moury et al [66] recently argued that they were also working on lithium hydrazinidoborane when Wu et al [32] published their experimental report. However, the former researchers were not able to compare favorably the structure of lithium hydrazinidoborane they mechano-synthesized to the compound proposed by later authors.…”
Section: Chemical Modification Of Hydrazine Boranementioning
confidence: 97%
“…However, the former researchers were not able to compare favorably the structure of lithium hydrazinidoborane they mechano-synthesized to the compound proposed by later authors. Moury et al [66] demonstrated that lithium hydrazinidoborane is a polymorphic material with a stable low-temperature phase with orthorhombic Pbca (61) space group, atoms standing in the 8c sites, and a metastable high-temperature phase as described by Wu et al [32]. The former was called the β phase because discovered after the metastable phase, then called α.…”
Section: Chemical Modification Of Hydrazine Boranementioning
confidence: 99%
See 1 more Smart Citation